Theme of Resistance in Rohinton Mistry’s A Fine Balance (Pravaha, 2021)
This research attempts to focus on the growing acts of resistance from the part of subalterns in A Fine Balance. Here, by criticizing the atrocities and perpetration of so-called upper class people and authorities over subalterns and showing the subaltern resistance, the writers try to show the growing subaltern consciousness in India. The marginalized characters undergo trial and tribulation in the novel. In the novel, Avinash is brutally murdered, Maneck commits suicide, Ishvar and Om are forced to undergo sterilization which leaves them deformed and destitute. Similarly, Dina loses her much needed independence and self respect and the society presented by Mistry is not an idealized one. Superstition, violence and gender inequalities are rampant. It is also the site of the repetition of caste-based brutality. The lower castes are beaten, tortured and killed for trivial reasons. By showing his characters in the position of resisting the brutalities and atrocities of upper class people and authorities, this research work argues that Mistry attempts to focus on the growing consciousness and resistance among subalterns in post-independent and Post Revolution Indian society, where subalterns want nothing but equality, justice, freedom, coexistence, and of course, communal harmony.